Congenital pseudarthrosis of the clavicle in an adult: case report and literature review - Diniz, Sara Elisa; Marques, Manuel Fernandes; Barros, Luís; Claro, Rui (International Journal of Research in Orthopaedics, 2021)
A 27 years old male, presented with a bump over the middle third of is right clavicle and a foreshortened shoulder girdle causing a severe deformity. Radiographs revealed a Congenital pseudarthrosis of the clavicle (CPC). A resection of the pseudarthrosis was carried and internal fixation with a reconstruction plate was done using iliac graft. One year after he was asymptomatic, without any functional impairment and very satisfied with the final cosmetic result. There is no consensus about optimal treatment. We present a rare case of surgical in an adult patient, and demonstrate why treatment must be individualized and surgical associated complications must be discussed.